BMP7 expression in the adult rat brain. (December 2017) - Kusakawa, Yuya; Mikawa, Sumiko; Sato, Kohji
Abstract: Bone morphogenetic protein-7 (BMP7), a member of the transforming growth factor-β (TGF-β) superfamily, has various effects in many biological events. However, there is little information on BMP7 expression in the adult central nervous system (CNS). Therefore, we investigated BMP7 levels in the adult rat CNS using immunohistochemistry. Abundant BMP7 expression was seen in astrocytes throughout the CNS and strong BMP7 expression was also observed in neuropils of the gray matter. Furthermore, BMP7 expression was observed in several kinds of neurons, including oxytocin, dopaminergic and noradrenergic neurons. These data suggest that BMP7 is widely expressed throughout the adult CNS, and support the idea that BMP7 plays pivotal roles in the adult brain, as well as in the developing brain. Highlights: BMP7 is expressed throughout the adult CNS, and abundantly expressed in astrocytes. BMP7 is also expressed in some kinds of neurons and axons.